The effect of immigration on some population genetic parameters of the Hungarian Hucul population - Somogyvári, Enikő; Posta, János; Mihók, Sándor (Acta Agraria Debreceniensis, 2017)
Population genetic indicators of the Hungarian Hucul population were calculated taking also into account the effect of imported horses.The birth year of the examined 3002 individuals ranged between 1871–2015. The last year involved in the examination was 2015, when the research was conducted on the stock under stud book control. The calculations on the population were made using the statistic indicators in the Endog programme, with and without the imported Polish horses. Figures were depicted using R software. Number of offspring of the Polish individuals was presented in tables; the distribution of the offspring per stud and per mare family, as well as the Nei’s genetic distance,were presented graphically.